2023
DOI: 10.1021/acs.est.3c02286
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced NH4+ Removal and Recovery from Wastewater Using Na-Zeolite-based Flow-Electrode Capacitive Deionization: Insight from Ion Transport Flux

Abstract: Flow-electrode capacitive deionization (FCDI) is a promising electromembrane technology for wastewater treatment and materials recovery. In this study, we used low-cost Na-modified zeolite (Na-zeolite) to prepare a composite flow-electrode (FE) suspension with a small amount of highly conductive carbon black (CB) to remove and recover NH 4 + from synthetic and actual wastewater (200 mg-N/L). Compared with conventional activated carbon (AC), the Na-zeolite electrode exhibited a 56.2−88.5% decrease in liquid-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Furthermore, the recyclability of adsorption performance was also investigated. As shown in Figure 8 d, after 5 cycles of reuse (recovery at 1 M KCl solution) [ 28 , 29 , 30 ], the ammonium adsorption performance of the obtained zeolite reaches a stable state and the ammonium removal rate reaches 34%. Compared with the first ammonium removal rate of 52%, it can be concluded that the ammonium exchange might occur just at the surface of the zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the recyclability of adsorption performance was also investigated. As shown in Figure 8 d, after 5 cycles of reuse (recovery at 1 M KCl solution) [ 28 , 29 , 30 ], the ammonium adsorption performance of the obtained zeolite reaches a stable state and the ammonium removal rate reaches 34%. Compared with the first ammonium removal rate of 52%, it can be concluded that the ammonium exchange might occur just at the surface of the zeolite.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is speculated that the FCDI combined with ion-exchange resin or zeolite developed in recent years cannot be used to treat brackish water with high SO 4 2− and Ca 2+ contents. 37,38 Brackish Water Softening in ISM-FCDI. The performance of ISM-FCDI for brackish water softening was evaluated (Figure 4a,b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The reaction medium comprised three distinct solutions: solution A containing 8.33 mM Na 2 H 2 PO 4 , solution B containing 12.3 mM FeCl 2 , and solution C containing either ultrapure water or NH 4 + at varying concentrations, depending on the specific experiment. In wastewater such as livestock one, digestion liquid, and landfill leachate, NH 4 + concentrations generally range from 150 to 1000 mg-N/L . Therefore, the initial concentration of NH 4 + was selected as 300, 600, and 800 mg-N/L.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphate-rich wastewaters, such as those from livestock wastewater, digestion liquid, and landfill leachate, serve as excellent phosphate sources for the vivianite crystallization method. However, besides phosphate, these wastewater typically contain ammonium (NH 4 + ), often reaching concentrations of several hundred milligrams per liter. , Considering the significance of NH 4 + in the phosphate recovery process through the vivianite crystallization method, this aspect is particularly crucial. Previous research has demonstrated that NH 4 + can exert an impact on mineral crystallization processes as well as on crystal morphology and structure.…”
Section: Introductionmentioning
confidence: 99%